Evaluation of Reaction Time during the One-Leg Balance Activity in Young Soccer Players: A Pilot Study - Fábio Saraiva Flôres; Joana Lourenço; Lucy Phan; Simon Jacobs; Renata Matheus Willig; Priscila Ellen Pinto Marconcin; Nuno Casanova; Denise Soares; Filipe Manuel Clemente; Ana Filipa Silva (MDPI AG, 2023)
This study's aim was two-fold: (i) to test the intra-session reliability of the one-leg balance activity test; and (ii) to assess the influence of age on reaction time (RT) and the differences between dominant and non-dominant feet. Fifty young soccer players with an average age of 12.4 ± 1.8 years were divided into two groups: younger soccer players (n = 26; 11.6 ± 0.9 years) and older soccer players (n = 24; 14.2 ± 0.8 years). Each group then completed four trials (two with each leg) of the one-leg balance activity (OLBA) to evaluate RT under a single-leg stance. Mean RT and the number of hits were calculated, and the best trial was also selected. T-tests and Pearson correlations were performed for statistical analysis. Values for RT were lower, and the number of hits was higher while standing on the non-dominant foot (p = 0.01). MANOVA revealed that the "Dominant Leg" factor did not affect the multivariate composite (Pillai Trace = 0.05; F(4, 43) = 0.565; p = 0.689; Partial ETA Squared = 0.050; Observed Power = 0.174). The "Age" factor did not present an effect on the multivariate composite (Pillai Trace = 0.104; F(4, 43) = 1.243; p = 0.307; Partial ETA Squared = 0.104; Observed Power = 0.355). The results of the present investigation demonstrate that RT may be lower while standing on the non-dominant foot.